Awareness and Adoption of Climate Resilient Horticulture Technologies by Farmers in Ri Bhoi District of Meghalaya - Barua, Utpal; Islam, Mokidul; Medhi, Samir (International Journal of Economic Plants, 2023)
A study was undertaken during the year 2020–2021 in Kyrdem and Sohriewblei villages, Ri-Bhoi district, Meghalaya, India to find out the level of awareness and adoption of climate resilient horticultural technologies. The selected villages had been adopted under National Initiative on Climate Resilient Agriculture (NICRA) project since 2011-2020. A sample size of 100 farmers (50 from each village) who were actively involved in horticultural activities was selected randomly. A well-structured, pre-tested interview schedule was employed for the data collection. The study revealed that the awareness level was recorded highest in institutional measures (94.2%) followed by horticultural practices (92.4%) and soil and water conservation (89%) measures. The highest adoption level of resilient practices was observed in horticultural practices (83.9%). Out of all respondents 89% were classified as medium category farmers for adoption of climate resilient technologies in both the villages. There was no statistical difference in the adoption level of resilient practices among the farmers of both the villages. Spearman rank correlation (0.730) depicted correlation between awareness and adoption level of horticultural technologies among the selected farmers in both the villages. It could be concluded that in an area like Meghalaya where small size of land holding and fragmented land emerged as main constraint for adoption of modern horticultural technology. Rigorous awareness programme to orient farming community towards scientific proven methods will be able to minimize the adverse effects of climate change.